Ansiedad y depresión en los pacientes con insuficiencia renal crónica en tratamiento de hemodiálisis en el Hospital Regional Isidro Ayora de la ciudad de Loja en el período marzo-agosto del 2013 - Guerra Adrianzen, Irina Milagros (2014)
This study aims to identify the Anxiety and Depression in Patients with Chronic Renal Failure, Regional Hospital Isidro Ayora city of Loja, during the period March-August 2013 This is a descriptive study, consisting of a universe of 65 patients of which by Inclusion criteria Exclusion sample was taken as 53 patients between 20 and 80 years old; them who were interviewed with the help of a questionnaire recording sociodemographic, clinical and risk factors of patients in study data was obtained, as well as the application of Test, The Hamilton Rating Scale for Anxiety and determine inventory Beck Depression II. According to the results it was determined that it is a generally they have in the main between 41-60 years of age, they are of masculine , resident in Loja's Province, is married, of primary instruction, self-supporting. The great majority has as disease base the Diabetes Mellitus and the period of treatment is bigger than 24 months. It was determined that the 58.5% had anxiety, generally it is Slight and are correlated to patients by ages understood 41- 60 years and a period of treatment bigger than 24 months. The 62.3% had depression, generally it is Moderate and are correlated to patients by ages understood 41- 60 years and a period of treatment bigger than 24 month, The factors of risk that intervene in the development process of Anxiety and Depression have: the No Work, economic dependence, Regular economic situation and the social exclusion. Keywords: Anxiety, Depression, Hemodialysis